2010
DOI: 10.1007/s10758-010-9172-8
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration into How Physical Activity Data-Recording Devices Could be Used in Computer-Supported Data Investigations

Abstract: There is a great potential opportunity to use portable physical activity monitoring devices as data collection tools for educational purposes. Using one such device, we designed and implemented a weeklong workshop with high school students to test the utility of such technology. During that intervention, students performed data investigations of physical activity that culminated in the design and implementation of their own studies. In this paper, we explore some of the mathematical thinking that took place th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 33 publications
(35 reference statements)
0
23
0
Order By: Relevance
“…This guidance was necessary for a variety of reasons. First, earlier work with this technology suggested that investigations with an uncertain outcome might promote more substantive discussions of data (Lee and DuMont 2010). Our concern for this study was that investigations which had easily predicted outcomes would lead to disengagement or lead to students misreading their data to conform with their anticipated conclusions (e.g., Kuhn 1989).…”
Section: Activity Cluster 3: Exploring and Investigating Heart Ratesmentioning
confidence: 98%
See 4 more Smart Citations
“…This guidance was necessary for a variety of reasons. First, earlier work with this technology suggested that investigations with an uncertain outcome might promote more substantive discussions of data (Lee and DuMont 2010). Our concern for this study was that investigations which had easily predicted outcomes would lead to disengagement or lead to students misreading their data to conform with their anticipated conclusions (e.g., Kuhn 1989).…”
Section: Activity Cluster 3: Exploring and Investigating Heart Ratesmentioning
confidence: 98%
“…Because they involve use during and for physical activities, we refer to these as PAD technologies (Lee and DuMont 2010). Canonical examples include pedometers, heart rate monitors, accelerometers, and distance trackers.…”
Section: What Are Pad Devices?mentioning
confidence: 99%
See 3 more Smart Citations